Satellite Remote Sensing Time-Series Observation of Russia–Ukraine War: Ongoing Conflict Increased Crop Risk - Yin Zhang; Qingwu Hu; Shaohua Wang; Pengcheng Zhao; Mingyao Ai (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Assessing the impact of the Russia–Ukraine war on crop growth is of great significance for the formulation of humanitarian aid and food security strategies. Based on nighttime light remote sensing data, we proposed a war intensity nighttime light index (WarINLI). The WarINLI was able to assess the conflict intensity in various Ukrainian oblasts and military conflict incidents quantitatively and accurately. It has high generalization and applicability to support the accurate estimation of war intensity. We evaluated crop growth status based on changes in vegetation indices derived from satellite remote sensing images. The degradation areas of four vegetation indices all accounted for over 73% of total cultivated land area. Integrating nighttime and daytime RS data, we explored the impacts of Russia–Ukraine war on the change of crop growth status through coupling coordination degree (CCD) model. The CCD between WarINLI variation and change rates of four vegetation indices was all greater than 0.75, which demonstrated that Russia–Ukraine war deteriorated crop growth situation and intensified crop risk in Ukraine. Our study provides a reference for government to initiate policy and supply relief so as to mitigate global food security threat.